2015
DOI: 10.22146/jpsi.7170
|View full text |Cite
|
Sign up to set email alerts
|

Mindset Wanita Pengusaha Sukses

Abstract: Many evidents show that women play important role in economic development of a region and a country. Any obstacles in business do not always inhibit them to be successful entrepreneur. This research was conducted to understand the nature of mindset owned by successful business women. The approach used was phenomenology to four respondents, who were female entrepreneurs. Data were collected by in-depth interview with them concerning food, drink, fashion and retails that were obtained through networking. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
3
0
7
Order By: Relevance
“…The findings of Goyal and Yadav (2014) show that the challenges faced by women entrepreneurs in developing countries include difficulties accessing financial resources as capital, socio-cultural factors and femininity, individual factors such as self-mistrust, government impartiality, lack of education and entrepreneurship skills. This is in accordance with the findings of Saputri and Himam (2015) based on research in Bangladesh, India, Indonesia and South Africa which concluded that women's constraints in entrepreneurship included problems (1) law, customs, traditions, culture and religion; (2) marital status; (3) heavy domestic work; (4) limited education, knowledge and information; (5) limited funds as capital, and access to credit; (6) inadequate institutional networks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of Goyal and Yadav (2014) show that the challenges faced by women entrepreneurs in developing countries include difficulties accessing financial resources as capital, socio-cultural factors and femininity, individual factors such as self-mistrust, government impartiality, lack of education and entrepreneurship skills. This is in accordance with the findings of Saputri and Himam (2015) based on research in Bangladesh, India, Indonesia and South Africa which concluded that women's constraints in entrepreneurship included problems (1) law, customs, traditions, culture and religion; (2) marital status; (3) heavy domestic work; (4) limited education, knowledge and information; (5) limited funds as capital, and access to credit; (6) inadequate institutional networks.…”
Section: Discussionsupporting
confidence: 89%
“…Study Saputri and Himam (2015) found a fourdimensional structure of women's entrepreneurial mindset, namely; (1) learning (2) spiritualism (3) interdependence, and (4) differentiation. The four dimensions of the mindset are manifested in behaviors such as (1) adaptation to constraints encountered, experiences facing failure and success; (2) involvement in social activities; (3) willingness to cooperate, and (4) interest in innovation and business development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berdasarkan data Badan Pusat Statistik (2014) jumlah wanita pengusaha di sebesar 5,86% pada tahun 2009 menjadi 7,91% pada tahun 2012. Tren wanita pengusaha sebesar 7,91% pada tahun 2012 berhasil melebihi tren pria pengusaha yang hanya sebesar 7,80% (Saputri, 2015).…”
Section: Wanita Pengusahaunclassified
“…Beberapa kendala seperti keterbatasan kemampuan dan kurangnya dukungan dan lingkungan membuat tantangan bagi wanita untuk terus melanjutkan perjuangannya (Aimasari & Ghina, 2015). Dibutuhkan adanya kemauan dan mental yang kuat untuk dapat menjalankan dan mempertahankan usahanya dengan baik (Saputri & Himam, 2015).…”
unclassified